Achiasmy: Male Fruit Flies Are Not Ready to Mix - John, Alphy; Vinayan, Kavya; Varghese, Jishy (Frontiers in Cell and Developmental Biology, 2016)
Maintenance of the chromosomal copy number over generations and recombination between homologous chromosomes is a hallmark of meiotic cell division. This genetic exchange that take place during gamete formation leads to genetic diversity, the main driving force behind natural selection. Formation of chiasmata, the physical link between homologous chromosomes during meiosis, is a requisite for recombination. In addition, chiasmata also aid in proper segregation of homologous chromosomes and has a major impact on reproductive fitness. Given these facts it is intriguing that many insect species have forgone the need for genetic exchange between homologous chromosomes during meiosis. Geneticists for several decades knew that meiotic crossover and recombination is absent in Drosophila males and some female lepidopterans, a condition termed achiasmy. However, currently a good understanding of the mechanisms that cause achiasmy and the evolutionary benefits of achiasmy is lacking. In this article we will discuss possible genetic and molecular basis of achiasmy in male Drosophila.